An amorphous-crystallization strategy towards high-quality graphene for constructing highly conductive Cu matrix composites - Guoqing Li; Wei Pan; Mengting Shi; Jingmei Tao; Xiaofeng Chen; Yichun Liu; Caiju Li; Jianhong Yi (Journal of Materials Research and Technology)
High-quality graphene (HQG)-Cu composites demonstrate remarkable properties; however, there remains a scarcity of preparation methods that are both simple and efficient for large-scale industrial application. Herein, amorphous graphene-like carbon (AGLC) synthesized on Cu powders using affordable solid carbon sources (SCS) was successfully converted into HQG inside the unconsolidated Cu skeletons by simple cold pressing combined with high-temperature hydrogen annealing technology. The HQG-Cu composites densified by spark plasma sintering exhibit repeatable high electrical and thermal conductivity (∼433 Wm−1K−1). Importantly, it demonstrates a remarkable enhancement of ∼23 % in thermal conductivity efficiency (per volume fraction of graphene). Compared with the original AGLC-Cu composites, the electrical conductivity of HQG-Cu composite has increased substantially, rising from 91.5 to 100.6 %IACS. Furthermore, such new design avoids the conflict between the high-temperature growth of HQG (above 1000 °C) and the welding of Cu powders (about 1000 °C). The conversion mechanism from SCS to HQG involving the competition between Cu catalysis and hydrogen etching is clearly revealed. Our research demonstrates the potential of SCS-converted HQG-Cu composites for industrial application, providing a promising avenue for further development of graphene-Cu composites.